Global Well-Posedness for the d-Dimensional Magnetic Bénard Problem without Thermal Diffusion - Yinhong Cao (Complexity)
This paper focuses on the global existence of strong solutions to the magnetic Bénard problem with fractional dissipation and without thermal diffusion in ℝd with d≥3. By using the energy method and the regularization of generalized heat operators, we obtain the global regularity for this model under minimal amount dissipation.